2015
DOI: 10.1371/journal.pone.0126422
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety and Tolerability of Melissa officinalis Extract which Contained Rosmarinic Acid in Healthy Individuals: A Randomized Controlled Trial

Abstract: The aim of this study was to evaluate the safety, tolerability and pharmacokinetics of single dose of Melissa officinalis extract which contained rosmarinic acid, including food-effects in healthy individuals. A total of eleven healthy individuals were randomly assigned to treatment arms in the two studies [Study 1 (fasted state) and Study 2 (fed state)]. Rosmarinic acid in serum was measured by a coulometric detection method using High-Performance Liquid Chromatography electrochemical detector. The serum conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 23 publications
3
69
4
Order By: Relevance
“…Reducing free-radicals from cigarette smoke by using a filter impregnated by an extract of a rosemary plant in oil was reported (Alexandrov et al 2006). Rosmarinic acid could exert its neuroprotective and anti-oxidative effects against 6-OHDA-induced neurotoxicity in dopaminergic neurons (Ren et al 2009;Wang et al 2012;Noguchi et al 2015). Our results also demonstrated that RE at dose of 50 mg/kg body weight could decrease oxidative stress by increasing the activities of SOD, CAT and GPx in hippocampus resulting in the decrease of lipid peroxidation level in lesioned region.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing free-radicals from cigarette smoke by using a filter impregnated by an extract of a rosemary plant in oil was reported (Alexandrov et al 2006). Rosmarinic acid could exert its neuroprotective and anti-oxidative effects against 6-OHDA-induced neurotoxicity in dopaminergic neurons (Ren et al 2009;Wang et al 2012;Noguchi et al 2015). Our results also demonstrated that RE at dose of 50 mg/kg body weight could decrease oxidative stress by increasing the activities of SOD, CAT and GPx in hippocampus resulting in the decrease of lipid peroxidation level in lesioned region.…”
Section: Discussionmentioning
confidence: 99%
“…1 filter paper (GE Healthcare Life Sciences, Pittsburgh, PA, USA). RA was identified from lemon balm (3.59% in lemon balm extract, LBE) as described previously [18].…”
Section: Plant Materials and Preparation Of Ramentioning
confidence: 99%
“…36 Acceptable daily intake (ADI) is a measure of the amount of a specific substance in that can be orally consumed on daily basis, over a lifetime without an appreciable health risk. 37 An ADI value can be calculated from the no observed adverse effect level (NOAEL). 37 In a study using AD model transgenic mice, RosA exhibited no adverse effect at a level of 1 g/kg in the study.…”
Section: Clinical Implications Safetymentioning
confidence: 99%
“…37 An ADI value can be calculated from the no observed adverse effect level (NOAEL). 37 In a study using AD model transgenic mice, RosA exhibited no adverse effect at a level of 1 g/kg in the study. 37 Assuming a human weight of 50 kg, NOAEL was determined as 50 g per day.…”
Section: Clinical Implications Safetymentioning
confidence: 99%